Turkey’s Role in Somalia’s Peace and Development Process - Oktay Bingöl (Gazi Akademik Bakış)
Somalia, as one of the poorest countries in Africa has been on the top list of the failed states, and tried to meet the challenges such as armed conflicts, poverty and mass migration since 1991. The attempts by the international community to ensure the peace and stability in Somalia have not produced the desired results by 2011. With the famine crisis in the 2011 summer, Turkey has initiated an opening towards Somalia. Turkey’s intervention and aids are soon welcomed by the people of Somalia and the expectations for the provision of the peace and stability have increased. Yet some critiques have arisen about Turkey’s policy toward Somalia. The critiques are focused on Turkey’s work in isolation from the international community, unawareness of Somali’s realities, the lack of institutional capacity and a long term strategy. The historical backdrop, social context and multi dimensional causes of the Somalia crisis indicate that the peace and stability can only be achieved by a long term and comprehensive work coordinated with all actors. In this context, Turkey should review the current Somalia policy and develop a comprehensive strategy